A residential well located inside a Parsi mansion - Mumbai Archive Project Team (Jio Institute, 2024)
Though Mazagon was an island with sea on all sides, it was well-known for freshwater resources. Before the days of municipally supplied tap water, there were a lot of wells and tanks that supplied drinking water. While some of these wells were privately dug within homes, others were open to the public. This covered well, for instance, is a private well located inside a Parsi mansion.